Contractual obligations in Civil Law of Ukraine: Executive points - Kostruba, Anatoliy (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The article explores the theoretical aspects of terminating civil obligations, emphasizing the unique role of contracts as legal facts. It asserts that contracts, established by parties in a legal transaction, serve as independent foundations for initiating, modifying, or terminating legal relations. The terms of civil contracts create distinct mechanisms for rightful termination, aligning with legal models for the occurrence of right-terminating legal facts. The author highlights the dependency of contractual obligations on the lawful intent of the involved party or objective circumstances, prescribed by the legal model in the contract. When these models align with actual events, they lead to the realization of parties' expectations and the termination of obligations. These legal facts contribute to the regulatory function of the law, ensuring the fair exercise of rights and interests as defined in the contract. The article provides a detailed list of such legal structures and conducts a legal analysis of their implications